IDENTITY AS THE TARGET OF INFORMATION WARFARE - Viktor Anatolyevich Avksentyev (Современная наука и инновации)
T is shown in the article that in the conditions of information warfare the role of the "soft power” in the impact on identity is diminishing. The information warfare is aimed at deconstructing the identity or transforming it into a negative identity, so the forming identity politics in Russia should include a set of measures aimed at countering information attacks on the all-Russian identity.